2022
DOI: 10.1039/d2qo00048b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-monosubstituted indolin-3-ones by cine-substitution of 3-azido-2-methoxyindolines

Abstract: We report herein the formal cine-substitution/hydrolysis of 3-azidoindole intermediates generated from 3-azido-2-methoxyindolines (AZINs). This protocol enables the introduction of both various carboxylic acid and alcohol into indolin-3-ones at the C2-position,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…Over the past five years, our group has had an intensive focus on the development and application of umpoled indole surrogates [33][34][35][36][37][38][39][40][41][42][43][44]. These results led us to find that in situ generated 3-methoxyindoles act as a C3-electrophilic reagent that can be harnessed for C-N, C-O, and C-C bond-forming SNAr reactions under indium catalysts [45,46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past five years, our group has had an intensive focus on the development and application of umpoled indole surrogates [33][34][35][36][37][38][39][40][41][42][43][44]. These results led us to find that in situ generated 3-methoxyindoles act as a C3-electrophilic reagent that can be harnessed for C-N, C-O, and C-C bond-forming SNAr reactions under indium catalysts [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…By analogy to our indium-catalyzed SNAr reaction, we hypothesized that N-alkoxy indoles might be suitable competent substrate as a N1-electrophilic indole precursor by a Lewis acid activation of alkoxy group through an elimination of ROH, thereby producing a C3-N1′ bisindole (Scheme 2). In this hypothesis, N-alkoxyindole is first combined with Lewis acids (LA) to form an LA-indole complex, which shows an N-electrophilic character by N-O bond activation along with reducing C3-nucleophilicity by coordinating at the C2-C3 π-bond [47- Over the past five years, our group has had an intensive focus on the development and application of umpoled indole surrogates [33][34][35][36][37][38][39][40][41][42][43][44]. These results led us to find that in situ generated 3-methoxyindoles act as a C3-electrophilic reagent that can be harnessed for C-N, C-O, and C-C bond-forming S N Ar reactions under indium catalysts [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Sawada's group reported a novel strategy for the preparation of 2-monoalkoxy indolin-3-ones via cine-substitution of 3-azido-2-methoxyindolines (Scheme 1b). 6 However, this protocol needs three steps to prepare the desired products from commercially available indoles, and only five desired products were obtained with accompanying formation of 2-monobenzoyloxy indolin-3-one or 2-monomethoxy indolin-3-one. In this scenario, more efficient and universal protocols for the preparation of 2-monoalkoxyindolin-3-ones from indoles under environmentally friendly conditions are highly interesting and desirable.…”
mentioning
confidence: 99%
“…Therefore, a key challenge in the formation of shewanelline C scaffold is the development of an appropriate nitrogen reagent containing an indoline moiety. We were interested in shewanelline C as part of our continuing efforts to develop a new application of 3-azido-2-methoxyindolines (AZINs) . We found that AZINs, which are 3-indolylazide equivalents, are effective for the ipso - or cine -substitution by nucleophiles with a release of N 2 to afford 3-substituted indoles or 2-monosubstituted indolin-2-ones.…”
mentioning
confidence: 99%
“…Treatment of protected indoles ( S1 ) with N -bromosuccinimide in MeOH afforded 3-bromo-2-methoxyindolines S2 . Subsequently, azidation of S2 with 5 equiv of NaN 3 in DMA led to the formation of AZINs ( 5 ) as the second nitrogen reagent . The reaction was relatively sensitive to the equivalents of NaN 3 , and reduction to <5 equiv resulted in a low yield.…”
mentioning
confidence: 99%